Driving Brand Evangelism Among Surabaya Gen Z through Brand Satisfaction, Passion, and Trust Towards Avoskin Beauty - Reni Jayanti; Rizky Dermawan (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
The decline in Avoskin's market share amid the intense competition in local skincare industry being serious concerns for the brand's sustainability. This research examines how brand satisfaction, brand passion, and brand trust influence brand evangelism among Generation Z towards consumers of Avoskin in Surabaya. Sample collected using a quantitative approach thought online questionnaire, with purposive sampling, involving 105 respondents who had used Avoskin products regularly for the past six months, Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) was employed to analyze the data using SmartPLS. The results indicate that brand satisfaction, brand passion, and brand trust have positive and significant effect on brand evangelism. These results finding the importance of customer satisfaction, emotional attachment, and trust in encouraging active loyalty and voluntary brand advocacy.